The impact of screen media portrayals of suicide on viewers: A rapid review of the evidence. (27th July 2020) - Posselt, Miriam; McIntyre, Heather; Procter, Nicholas
Abstract: This rapid review aimed to review recent published literature and describe the current evidence regarding the impact, on viewers, of portrayals of suicide in screen/ moving‐image fiction and non‐fiction media, such as television/web series, films and documentaries. We searched various databases for research conducted within the past decade (2009–2019). A total of 16 articles were eligible for inclusion. The literature reported varying impacts of portrayals of suicide through moving‐image media such as increased suicidal ideation and behaviour, as well as positive impacts such as increased help‐seeking behaviour. While there is limited evidence which focuses specifically on the impact of moving‐image media, the studies included in this review highlight concerning trends regarding the impact of media portraying deaths by suicide on subsequent suicidality. However, positive impacts on suicide awareness, literacy and help‐seeking behaviour were also identified.